Is the classification of athletes based on force-velocity profiling from countermovement jumps influenced by the choice of method? - Paulsen, G.; Lindberg, K.; Eriksrud, O.; Solberg, P.; Bjørnsen, T.; Seynnes, O.; Gløersen-Haga, Ø.; Bobbert, M.; Rice, H. (Medicine & Science in Sports & Exercise, 2025)
Purpose Force-velocity (FV) profiling is a tool for classifying athletes as force- or velocity-deficient, allowing for tailored training prescriptions. However, profiling classification may vary depending on the measurement method used. This study compared FV profile variables derived from countermovement jumps (CMJs) using four approaches: the Flight-time method, a Kinetic method, and two kinematic methods.